Antimicrobial activity of an L-amino acid oxidase isolated from Bothrops leucurus snake venom - Torres,AFC (2010)
Some snake venom proteins present enzymatic activities, such as L-amino acid oxidase (LAAO). The aim of this paper was to investigate the effect of Bothrops leucurus total venom (BleuTV) and its fraction LAAO (BleuLAAO) on bacteria, yeast, and promastigote forms of Leishmania amazonensis and Leishmania chagasi, and epimastigote forms of Trypanosoma cruzi. BleuTV was isolated with a Protein Pack 5PW® (Waters Corporation, USA), and several fractions were obtained. BleuLAAO was purified to high molecular homogeneity, and its N-terminal amino acid sequence shared a high degree of amino acid conservation with other LAAOs. BleuTV inhibited Staphylococcus aureus growth in a dose-dependent manner, with a minimum inhibitory concentration (MIC) of 25 μg/mL, which corresponded to its minimum lethal concentration (MLC). BleuTV also inhibited the growth of promastigote forms of L. chagasi and L. amazonensis, with respective IC50 values of 1.94 μg/mL and 5.49 μg/mL. Furthermore, it repressed T. cruzi growth with an IC50 of 1.14 μg/mL. However, BleuLAAO did not inhibit the growth of the microorganisms studied and was not toxic to macrophages. BleuTV had low toxicity against macrophages at the concentrations studied. In conclusion, whole venom from Bothrops leucurus inhibited the growth of some microorganisms, including S. aureus, Leishmania sp., and T. cruzi.